Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content 1. The impact of using the Edmodo educational platform on the development of cognitive achievement and motivation towards learning mathematics among eleventh grade students in the governorate of South Al Batinah in Sultanate of Oman Mr. Fahad Moosa Anas Al- Bhri 2. Effectiveness of stories in developing the environmental awareness of the kindergarten child in Hafar Al-Batin governorate Mrs. Hannan Matar Suhman Al-Anzi’s 3. The Effect of The Electronic Mind Maps as A Pre and Post Graphic Organizer in The Development of Computational Concepts among Middle School Students Mr. Muaadh Mohammed Hamid Almagedi 4. Analysis of the content of the mathematics book for the fifth grade of primary school in the light of the criteria of integrative organization in the Kingdom of Saudi Arabia Mrs. Somayya Mohammad Al-Shehri, Dr. Mounira Al-Salal 5. The impact of E-learning support through smart chatbots enhancing academic performance and happiness across educational platforms for secondary school students Mr. Waleed Homou Aljeraisy 6. The degree of including assessment activities for the skill of creative flexibility in the Arabic language textbook for the twelfth grade in the Sultanate of Oman Dr. Wafa Salim Mohammed Alshamsi, Co-Prof. Amal Mahmoud Ali 7. The attitudes of faculty members and students at King Saud University towards the use of microlearning Mrs. Al-Maha Ali Al-Qahtani, Dr. Latifah Khalil Al-Ateeq